Urine Haptoglobin/Creatinine Ratio Correlates with Tubular Injury Biomarkers and Severity of Albuminuria in Type 2 Diabetes Patients - Wang, Yangyang; Zhou, Qianying; Zhang, Lijun; Dai, Yali; Huang, Zhijun; Zhang, Hao; Yi, Bin (Hormone and Metabolic Research, 2019)
This aim of this study was to investigate the correlation between urine haptoglobin/creatinine ratio(UHCR) and tubular injury biomarkers or severity of albuminuria in type 2 diabetes. Recruited T2DM patients (n=120) were divided into three groups based on urine albumin/creatinine ratio (UACR): normal albuminuria (Normo group, UACR<30 mg/g, n=40), microalbuminuria (Micro group, 30 mg/g ≤UACR<300 mg/g, n=38), and macroalbuminuria (Macro group, UACR ≥300 mg/g, n=42), with matched healthy individuals (NC group, n=30) as controls. ELISA assay was used to detect the levels of urine haptoglobin, NGAL and KIM-1. Automated biochemical analyzer was applied to detect the concentrations of urine creatinine and retinol binding protein (RBP). To eliminate concentration errors, urine NGAL, KIM-1, and RBP were normalized by creatinine and expressed as UHCR, UNCR, UKCR, and URCR, respectively. We found UHCR was significantly increased in T2DM patients as compared with NC group. Among the three diabetic groups, the Macro group had the highest level of UHCR, whereas the Normo group had the lowest level. T2DM patients with higher UHCR levels also had higher levels of UNCR, UKCR, and URCR. Spearman’s correlation analysis indicated that UHCR was positively correlated with UACR, UNCR, UKCR, or URCR levels, and negatively correlated with eGFR. ROC curve analysis showed that UHCR was a sensitive and specific indicator for early diagnosis of DN. Stepwise multiple regression analysis showed that UHCR and UNCR were independent variables for UACR. Our research demonstrated that UHCR correlates with tubular injury biomarkers, including UNCR, UKCR, and URCR, and is independently associated with the severity of albuminuria in T2DM.
Keywords: urine haptoglobin; type 2 diabetic nephropathy; tubular injury biomarkers; albuminuria